2020
DOI: 10.1101/2020.06.17.158493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Portieragives new clues on the evolutionary history of whiteflies

Abstract: Whiteflies (Hemiptera:Sternorrhyncha: Aleyrodidae) are a superfamily of small phloem-feeding insects.Their taxonomy is currently based on the morphology of nymphal stages that display phenotypic plasticity, which produces inconsistencies. To overcome this limitation, we developed a new phylogenetic framework that targets five genes of Candidatus Portiera aleyrodidarum, the primary endosymbiont of whiteflies. Portiera lineages have been co-diverging with whiteflies since their origin and therefore reflect their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…As a result, there is likely to be tremendous variation among the symbiont genomes of closely related host species. For example, the process of drift is known to cause independent symbiont lineages to differ widely in their genetic capabilities even between closely related host species (McCutcheon and Moran, 2010;Patin ˜o-Navarrete et al, 2013;Husnik et al, 2013;Campbell et al, 2015Campbell et al, , 2017Bennett et al, 2016b;Husnik and McCutcheon, 2016;Boscaro et al, 2017;Łukasik et al, 2018;Chong et al, 2019;Monnin et al, 2020;Santos-Garcia et al, 2020). It is less clear how drift and selection work together to shape and maintain the genes and functions of symbionts as they diversify along with their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is likely to be tremendous variation among the symbiont genomes of closely related host species. For example, the process of drift is known to cause independent symbiont lineages to differ widely in their genetic capabilities even between closely related host species (McCutcheon and Moran, 2010;Patin ˜o-Navarrete et al, 2013;Husnik et al, 2013;Campbell et al, 2015Campbell et al, , 2017Bennett et al, 2016b;Husnik and McCutcheon, 2016;Boscaro et al, 2017;Łukasik et al, 2018;Chong et al, 2019;Monnin et al, 2020;Santos-Garcia et al, 2020). It is less clear how drift and selection work together to shape and maintain the genes and functions of symbionts as they diversify along with their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, insect microbiota are known to detoxify noxious secondary metabolites and xenobiotics, such as terpenes (Berasategui et al, 2017), caffeine (Ceja-Navarro et al, 2015;Summers et al, 2015), nicotine (Brandsch, 2006), and insecticides; defending against parasites and other pathogens; generating and relaying signals among hosts; improving behavior and immunity; and producing nutrients to supplement host's diet and to enhance their digestion (Dillon and Dillon, 2004;Ezemwa et al, 2012;Wu et al, 2016). In recent years, a growing number of studies have cataloged and characterized microbial communities, particularly in bees (Moran et al, 2012), fruit flies (Erkosar et al, 2017;Bing et al, 2018), termites (Rossmassler et al, 2015), silkworm (Chen et al, 2018), whiteflies (Santos-Garcia et al, 2020), and beetles (Kudo et al, 2018). For example, Zhang et al (2022) found that a normal gut microbiota is required for olfactory learning and memory abilities, mainly by regulating tryptophan metabolism, with host-specific Lactobacillus strains enhancing memory by transforming tryptophan to indole derivatives that activate the host aryl hydrocarbon receptor in honeybee (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%